Do Pre-service Chemistry Teachers’ Collective Pedagogical Content Knowledge Regarding Solubility Concepts Enhance after Participating in a Microteaching Lesson Study? - Yezdan Boz; Hatice Belge-Can (Science Education International, 2020)
The purpose of this study was to investigate the influence of a microteaching lesson study on pre-service chemistry teachers’ collective pedagogical content knowledge (PCK) regarding solubility concepts. Three pre-service chemistry teachers participated in this study. Data were collected by means of lesson plans, semi-structured interviews, observations, and field notes. Results indicated that participants’ PCK shows uneven development in terms of its components. Specifically, pre-service chemistry teachers’ collective PCK was developed in all subcomponents with respect to the knowledge of instructional strategies component whereas only in some of the subcomponents with respect to the knowledge of curriculum, learner, and assessment. Time of assessment, knowledge of students’ alternative conceptions, and knowledge of the goals and objectives of the curriculum were the subcomponents changed in terms of knowledge of assessment, knowledge of learner, and knowledge of curriculum, respectively. Reflection on action, content knowledge, pedagogical knowledge, and previous experiences of participants were determined as factors influencing their collective PCK development. The present study has several implications for teacher educators.